Struktur Puisi dan Makna Kesempurnaan dalam Lirik Lagu “Pelukku Untuk Pelikmu” karya Fiersa Besari dan “Sempurna” karya Andra and The Backbone - Roy, Arya; Purnomo, Mulyo Hadi; Mukafi, Muhammad Hamdan (Fakultas Ilmu Budaya Universitas Diponegoro, 2025)
Abstract This study analyzes the structure and the meaning of perfection in the song lyrics “Pelukku untuk Pelikmu” by Fiersa Besari and “Sempurna” by Andra and the Backbone. The aim of this research is to reveal how the lyrical elements reflect the concept of perfection. The research approach employs Roman Ingarden's theory of normative strata, which consists of five layers: the sound layer, the meaning layer, the object layer, the world layer, and the metaphysical layer. In addition to Ingarden's theory, this study also applies Hewitt and Flett’s theory of perfectionism, which includes three dimensions: self-oriented, other-oriented, and socially prescribed perfectionism. The analysis shows that “Pelukku untuk Pelikmu” emphasizes acceptance of human imperfections through self-acceptance of one's partner. In contrast, “Sempurna” portrays an idealized view of a partner as a perfect figure, strengthening the emotional bond within the relationship. Both songs present different interpretations of perfection, yet both focus on the value of appreciation in human relationships. This study is expected to enrich the understanding of how perfection is perceived in literary works, particularly in song lyrics, and to contribute to the study of Roman Ingarden's normative strata analysis and the concept of perfectionism. Keywords: song lyrics, structural, perfection, perfectionism